Managing Relational Capital for the Sustainability of the Energy Sector in the Social Media - Ana-María Casado-Molina; Célia M.Q. Ramos; Francisco Cabrera (Tourism & Management Studies)
Various management models have been proposed for intangible business assets in this new digital era. However, these models do not consider the relationships between intangible assets in business management, or their effect. This work has two main objectives: first, to show the effect of intangi-ble assets as expressed in digital media related to energy brands; second, to demonstrate the rela-tionships between the emotions, experiences and attitudes of the audiences. To do so, a novel model of intangibles is proposed and applied to the energy sector using IBEX 35 data. In this sce-nario, we determine that users’ experiences extracted from digital environments have significant relationships with one of the most important intangibles in the energy business, namely emotion.